In-flight transmission of SARS-CoV-2: a review of the attack rates and available data on the efficacy of face masks - Freedman, David O.; Wilder-Smith, Annelies (Journal of travel medicine, 2020)
In-flight transmission of SARS-CoV had previously been demonstrated during the symptomatic but not asymptomatic phase of illness. In 2003, up to 22 transmissions occurred on a single flight from a single index case;1 conversely, several other carefully studied flights resulted in no transmission. SARS-CoV-2, the novel coronavirus that shares 86% homology with SARS -CoV, differs in having both significant transmission from pre-symptomatic and asymptomatic persons as well as secondary cases that may remain asymptomatic even with a 14-day follow-up period. At the same time, cases secondary to in-flight transmission may be detected in as few as 3 days post-flight. As timing is so critical, the burden of absolute proof for ascertaining in-flight transmission risk is high. A possible secondary case, who presents with COVID-19 symptoms, or is detected as an asymptomatic person with a positive COVID-19 PCR several days after arriving at their destination, could have been infected: (i) in the days before departure from the flight origination point; (ii) en-route to the airport; (iii) while at the airport; (iv) on the flight or even (v) on/after arrival at the destination airport.
Gesehen am 03.04.2022